The Impact of Student Ethics on Learning Outcomes in Elementary Schools - Bella Karina; Luthfiyah Apriani (Journal on Education, 2024)
This study investigates the impact of student ethics on learning outcomes at SD Negeri 30 Pagar Alam using a quantitative survey methodology. Quantitative research involves larger samples and a systematic approach throughout. Data was collected from 222 students, with a sample size of 22, using observation, interviews, documentation, and questionnaires. The analysis included validity tests, reliability tests, simple linear regression hypothesis testing, and questionnaire score examination. The findings show a significant relationship between student ethics and learning outcomes, with a correlation coefficient (r) of 0.494 and a significance level of 0.019 below 0.05, indicating a strong correlation. The reliability test for variable X yielded 0.6200. The t-test result (2.543) exceeded the t-table value (2.086), demonstrating a significant impact of student ethics on learning outcomes, thus rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). Factors influencing student ethics include individual characteristics, personal interests, concentration in studying, and the peer environment.